Influence of Terrestrial Parameters on the Ecophysiological Composition of Young Plants Kahya Senegalensis in Saline Environment - Campos, Willian Viana; Filho, José Teixeira; José, Alcebíades Rebouças São (Journal of Agricultural Studies, 2024)
This study aims at analyzing the behavior of young African mahogany plants in a saline environment, focusing on perceptions related to transpiration, photosynthetically active radiation and water potential. The experiment was conducted in drainage lysimeters, using different salinity levels of irrigation water. Environmental data, such as photosynthetically active radiation, water potential and electrical conductivity, were collected to investigate their influence on the transpiration of African mahogany plants. The research was carried out in an experimental field in the northeast region of Brazil, over a period of four months, with young African mahogany plants (Khaya senegalensis), using water with an electrical conductivity of 0.5 dS.m -1 (control treatment); 1.25 dS.m -1; 2 dS.m -1; 2.75 dS.m -1; 3.5 dS.m -1; 4.25 dS.m -1 and 5 dS.m -1 in a total of seven treatments, with three replications and 21 experimental units (plants). Plant transpiration was measured using a steady-state diffusion porometer. The electrical conductivity of the irrigation water was monitored using a portable conductivity meter. The results presented in the analyzes indicate a complex and interdependent relationship between leaf transpiration, photosynthetically active radiation and plant water potential. Leaf transpiration is influenced by variations in solar radiation, which plays a crucial role in regulating this process. It was observed that leaf transpiration is lower in the morning, from 7 to 9 am and in the late afternoon, from 5 to 6 pm, when incident solar radiation is at lower values.